Effect of FTO Gene and Physical Activity Interaction on Trunk Fat Percentage Among the Newfoundland Population. (January 2014) - Payne, Anthony; Cahill, Farrell; Sun, Guang; Loredo-Osti, J Concepción; Abarin, Taraneh
Objective: To explore the effect of FTO gene and physical activity interaction on trunk fat percentage. Design and Methods: Subjects are 3, 004 individuals from Newfoundland and Labrador whose trunk fat percentage and physical activity were recorded, and who were genotyped for 11 single-nucleotide polymorphisms (SNPs) in the FTO gene. Subjects were stratified by gender. Multiple tests and multiple regressions were used to analyze the effects of physical activity, variants of FTO, age, and their interactions on trunk fat percentage. Dietary information and other environmental factors were not considered. Results: Higher levels of physical activity tend to reduce trunk fat percentage in all individuals. Furthermore, in males, rs9939609 and rs1421085 were significant (α = 0.05) in explaining central body fat, but no SNPs were significant in females. For highly active males, trunk fat percentage varied significantly between variants of rs9939609 and rs1421085, but there is no significant effect among individuals with low activity. The other SNPs examined were not significant in explaining trunk fat percentage. Conclusions: Homozygous male carriers of non-obesity risk alleles at rs9939609 and rs1421085 will have significant reduction in central body fat from physical activity in contrast to homozygous males of the obesity-risk alleles. The additive effect of these SNPs is found in males with high physical activity only.